2019
DOI: 10.1371/journal.pone.0222911
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant profile and prevalence of extended spectrum β-lactamase and carbapenemase production in fermentative Gram-negative bacilli recovered from patients and specimens referred to National Reference Laboratory, Addis Ababa, Ethiopia

Abstract: BackgroundThe emergence of multidrug-resistance (MDR), production of extended-spectrum β-lactamases, and carbapenemase in members of fermentative gram-negative bacilli are a serious threat to public health.ObjectiveThe aim of this study was to determine the burden of multi-drug resistance, the production of extended-spectrum β-lactamases (ESBLs), and carbapenemase in fermentative Gram-negative bacilli in Ethiopian Public Health Institute.Materials and methodsA cross-sectional study was carried out from Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
47
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 38 publications
28
47
19
Order By: Relevance
“…The pooled proportional estimate of resistance against third-generation cephalosporins (cefotaxime and ceftazidime), amoxicillin-clavulanic acid, gentamicin, ciprofloxacin, SXT and TET ranges from 43.8% to 79.0%. Almost similar findings were reported in Ethiopia and Chile, in which 45.4% to >88% isolates exhibit resistance against beta-lactams and non-lactam drugs ( 33 , 48 ). This high resistance rate might be associated with an interesting feature of ESBL-producing isolates as resistance mechanisms, which may be either chromosomally or plasmid-encoded, especially CTX-M that often showed feature of coresistance to various classes of antibiotics such as fluoroquinolones, aminoglycosides, and co-trimoxazole.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The pooled proportional estimate of resistance against third-generation cephalosporins (cefotaxime and ceftazidime), amoxicillin-clavulanic acid, gentamicin, ciprofloxacin, SXT and TET ranges from 43.8% to 79.0%. Almost similar findings were reported in Ethiopia and Chile, in which 45.4% to >88% isolates exhibit resistance against beta-lactams and non-lactam drugs ( 33 , 48 ). This high resistance rate might be associated with an interesting feature of ESBL-producing isolates as resistance mechanisms, which may be either chromosomally or plasmid-encoded, especially CTX-M that often showed feature of coresistance to various classes of antibiotics such as fluoroquinolones, aminoglycosides, and co-trimoxazole.…”
Section: Discussionsupporting
confidence: 82%
“…III ). This finding is higher than a finding of previous meta-analysis in Ethiopia, in which the pooled proportional estimates of MDR isolates were 59.7% ( 47 ); however, it was lower than a single study finding in Ethiopia ( 33 ) and Chile ( 48 ), in which 94.5% and 100% isolates exhibited MDR profiles. Lower study finding was also reported in Ethiopia, in which the overall prevalence of MDR was 69.9%, of which 81.5% was in the hospital environment, while 54.2% was in non-hospital environment samples ( 49 ).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Some researchers reported that the same result and stated that the frequency of β-lactamases in XDR strains is higher than MDR ones. 1,3,30,31 However, to increase the predictive value of this association, precise and sensitive molecular methods should be used in epidemiological studies. 32 In this study, we developed an HRMA assay for the detection of ESBL producing, KPC-producing, and CRPA strains by melting curve analysis technology.…”
Section: Discussionmentioning
confidence: 99%
“…The low bacterial resistance to ertapenem might be due to its relatively new administration and low rate of prescription for infectious illness. Studies in Ethiopia and Colombia also reported low resistance to ertapenem [40,41].…”
Section: Antibiotic Nonsusceptibilitymentioning
confidence: 99%